Realizing a Village Without Poverty: The Challenges of Implementing the Village SDGs Policy in Indragiri Hilir Regency, Riau Province - Alkadafi, Muammar (KnE Social Sciences, 2022)
Indragiri Hilir Regency is an autonomous region in Riau Province, which in 2020 had the second highest level of poverty in the region (13.10%). This level of poverty was not directly proportional to the wealth of natural resources in the village. The purpose of this study was to determine the contribution of development and village empowerment programs in alleviating poverty and the challenges of realizing SDG goal 1 in the Indragiri Regency. Qualitative research methods were used and data were collected through a literature review of related studies and reports on the achievements of the SDGs program. The results showed that the village government could not carry out the tasks and functions of empowering the poor in their village. Empowerment programs carried out by local governments did not focus on strengthening the capacity of the poor. Keywords: hallenges, policy implementation, village SDGs, poor community